Fractography of chopped fiber glass reinforced epoxy composite at +50°C and -50°C under dynamic impact loading / Nazrin, A., Mridha, S. and Rahman, M.A. - A., Nazrin; S., Mridha; M.A., Rahman (2006)
Hand lay up process was used to fabricate the chopped fiber composite containing 52 vol% fiber fraction. The impact Testing for fracturing the samples was conducted using Charpy impact test at +50°C and -50°C. The energy to fracture the specimens was found to decrease with reduced temperature. The sample broke at +50°C gave plastic deformation with mixed fracture mode of cracked fiber bundles, buckling and fiber splitting. While at -50°C the fractured specimens gave the same plastic deformations but with more fibers splitting than that tested at +50°C. The failures were concentrated at pendulum striking areas and V notch areas. These failures caused by compressive stress at striking areas and tensile stress at notch areas. Fiber protrusion was seen in samples tested at both temperatures and It happened because of short fiber filaments. The short fiber filaments gave easier matrix cracking at short distances and this may be one of the reasons of having lower energy absorption compared to the continuous woven fiber.